2002
DOI: 10.2466/pms.2002.95.3.747
|View full text |Cite
|
Sign up to set email alerts
|

Practice Effects on Reaction Time for Peripheral and Central Visual Fields

Abstract: The present study examined whether EMG-RT (RT) for a key press to stimulus in peripheral and central visual fields decreases with practice. 16 male students were divided into two groups, one practicing using peripheral vision, the other practicing using central vision. Before and after practice, RT was measured for peripheral and central visual fields. Each group practiced three blocks of 25 trials five days a week for three weeks. RT for peripheral and central visual fields decreased with practice. Practice e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 16 publications
0
41
1
2
Order By: Relevance
“…(7) One plausible mechanism for this decrease in reaction time is that an increased heart rate due to moderate exercise increases cortical blood flow and enhances cognitive function due to a greater state of arousal. (15) Another study reported an improvement in reaction times irrespective of age and gender when subjects regularly exercised for 30 minutes in gymnasium. (3) Exercise training increases mitochondrial content of exercising muscles delaying fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…(7) One plausible mechanism for this decrease in reaction time is that an increased heart rate due to moderate exercise increases cortical blood flow and enhances cognitive function due to a greater state of arousal. (15) Another study reported an improvement in reaction times irrespective of age and gender when subjects regularly exercised for 30 minutes in gymnasium. (3) Exercise training increases mitochondrial content of exercising muscles delaying fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…As differences between RT values obtained in the center and periphery as well as nasal and horizontal parts of the visual field have been reported [31] , two RT vectors were presented in the central and another two in the peripheral seeing area of the visual field (one in the superotemporal quadrant and one along the nasal horizontal meridian).…”
Section: Visual Field Examinationmentioning
confidence: 99%
“…The visual signals (vivid light) were slightly peripheral to the central visual field, in order to potentially speed up sensor motor reaction [38]. At the instant the light was switched on the electromagnetic arresters were simultaneously deactivated and the lever was able to move freely.…”
Section: Methodsmentioning
confidence: 99%
“…Measurement of RT was conducted under standard experimental conditions [8,31,[38][39][40] and others]. The study of the latent period of simple sensor motor reaction was performed using a specific instrument called a computer movement meter ("KMM") pro duced by the company INTOKS (St. Petersburg), Registration Certificate Number 29/03041202/5085 03 April 11, 2003.…”
Section: The Main Experimentsmentioning
confidence: 99%